К устойчивости основного движения двухмаятникового автобалансира - Филимонихин, Г. Б.; Філімоніхін, Г. Б. (My University, 1996)
Dynamic stability of the main motion of a two-pendulum autobalancing device is studied within the plane model. The sufficient conditions of asymptotic stability are found for the cases where the pendulum mass, is much less than that of the rotor at large friction between pendulums and the rotor shaft, under large external damping, and under high-speed rotation of the rotor. For small damping, one or three critical speeds are found and the region of stability of the main motion is constructed which is independent of disbalance of the rotor.
Keywords: устойчивость; основное движение; автобалансир; первое приближение; метод малого параметра; критические скорости